Dual career in European-funded projects: a critical analysis and review - Flavia Guidotti; Daniele Conte; Lucia Bertocchi; Mojca Doupona; Laura Capranica (Colégio Brasileiro de Ciências do Esporte, 2023)
ABSTRACT This study aimed to review the projects financed between 2014 and 2022 under the ERASMUS+ programme of the European Commission to examine the past and present implementation of the dual career (DC) of elite sportspersons and to highlight potential gaps to guide future project proposals. Findings showed a relevant focus of the financed projects on the micro and multi-dimensional aspects of DC of athletes as the main target group, implementing training courses/programmes in different settings, and partnerships mostly composed by educational institutions and NGOs. In the future, sports bodies should engage more in partnerships, whereas DC of employee-sportspersons as athletes and sports staff should be implemented, with a strong focus on the project's long-term impact and sustainability.